Antibacterial Activity of Rhizome Extracts of Zingiber zerumbet (L.) Roscoeex Sm. Against Streptococcus pneumoniae: Aktivitas Antibakteri Ekstrak Rimpang Lempuyang Gajah (Zingiber zerumbet (L.) Roscoeex Sm.) Terhadap Bakteri Streptococcus pneumoniae - Rohmah, Jamilatur; Rini, Chylen Setiyo (Universitas Muhammadiyah Sidoarjo, 2022)
Research on the antibacterial activity of the ethanolic extract of lempuyang (Zingiber zerumbet (L.) Roscoe ex Sm.) against Streptococcus pneumoniae has been carried out using the disc diffusion method. Streptococcus pneumoniae is a bacterium that can cause respiratory tract infections (ARI), in its handling, people use antibiotics. Antibiotics themselves if used continuously lead to resistance. Currently, there are many studies regarding traditional medicines as antibacterials. The purpose of this study was to determine the secondary metabolite content of lempuyang elephant rhizome and to determine the antibacterial activity of lempuyang extract on Streptococcus pneumoniae bacteria. The method used in this research is the diffusion method with paper discs to determine the inhibitory power. The lempuyang plants used were obtained from the village of Tegal Bulu Banyuwangi and isolates of S. pneumoniae were obtained from the Central Health Laboratory (BBLK) Surabaya. The concentrations of the extracts used were 20, 40, 60, 80, and 100% with a positive control of chloramphenicol. The results showed that the ethanol extract of lempuyang (Zingiber zerumbet (L.) Roscoe ex Sm.) could inhibit the growth of S. pneumoniae bacteria, which was known from the inhibition zone formed. The inhibition test showed that the higher the concentration of lempuyang extract, the larger the diameter of the inhibitor formed. In lempuyang, the highest inhibition diameter was found at a concentration of 100% at 43.9 ± 3.6 mm. The results of phytochemical testing showed that the ethanol extract of lempuyang (Zingiber zerumbet(L.) Roscoe ex Sm.) contained alkaloids, flavonoids, saponins, steroids, triterpenoids, phenolics, and tannins.